Aminobenzimidazoles and Structural Isomers as Templates for Dual‐Acting Butyrylcholinesterase Inhibitors and hCB2R Ligands To Combat Neurodegenerative Disorders. (9th November 2015) - Dolles, Dominik; Nimczick, Martin; Scheiner, Matthias; Ramler, Jacqueline; Stadtmüller, Patricia; Sawatzky, Edgar; Drakopoulos, Antonios; Sotriffer, Christoph; Wittmann, Hans‐Joachim; Strasser, Andrea; Decker, Michael
Abstract: A pharmacophore model for butyrylcholinesterase (BChE) inhibitors was applied to a human cannabinoid subtype 2 receptor ( h CB2 R) agonist and verified it as a first‐generation lead for respective dual‐acting compounds. The design, synthesis, and pharmacological evaluation of various derivatives led to the identification of aminobenzimidazoles as second‐generation leads with micro‐ or sub‐micromolar activities at both targets and excellent selectivity over h CB1 and AChE, respectively. Computational studies of the first‐ and second‐generation lead structures by applying molecular dynamics (MD) on the active h CB2 R model, along with docking and MD on h BChE, has enabled an explanation of their binding profiles at the protein levels and opened the way for further optimization. Dual‐acting compounds with "balanced" affinities and excellent selectivities could be obtained that represent leads for treatment of both cognitive and pathophysiological impairment occurring in neurodegenerative disorders. Abstract : Two in one : In this study dual‐acting compounds were identified and optimized, and binding modes were computationally investigated to yield ligands that can bind selectively to the cannabinoid receptor 2 (CB2 R) and inhibit butyrylcholinesterase (BChE) in the same concentration range. Such compounds serve as leads for multitarget drugs acting at both GPCRs and enzymes for therapeutic application in neurodegenerative disorders.